(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Reading and writing skills contribute significantly to all the formative stages of the human being; however, there are students who finish primary school without reading and writing well. This research reports on a pedagogical proposal developed at the Santa María Departmental Educational Institution in Ubaté, whose objective was to promote writing as a process composed of stages called time for reading, planning, writing, revising, correcting, sharing, rewriting and publishing in fifth grade students. The action-participation methodology was used. The results highlight the creation of a printed magazine composed of 82 traditional stories with their respective workshop, as well as the writing of 65 stories authored by the participants in the rewriting stage for possible publication. It is also evident that 91% of the parents read all the stories in the company of their daughters during 4 months; therefore, the reading speed of the students improved, since they went from 82 words per minute to 122 on average.